2010
DOI: 10.1007/s00332-010-9069-7
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Conservation Laws with Nonconstant Coefficients with Application to Particle Size Segregation in Granular Flow

Abstract: Granular materials will segregate by particle size when subjected to shear, as occurs, for example, in avalanches. The evolution of a bidisperse mixture of particles can be modeled by a nonlinear first order partial differential equation, provided the shear (or velocity) is a known function of position. While avalanche-driven shear is approximately uniform in depth, boundary-driven shear typically creates a shear band with a nonlinear velocity profile. In this paper, we measure a velocity profile from experime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Bridgwater, Foo & Stephens 1985;Savage & Lun 1988;Bridgwater 1994;Dolgunin & Ukolov 1995;Gray & Thornton 2005;Gray & Chugunov 2006;Thornton et al 2006;May, Shearer & Daniels 2010) all share a similar advection-diffusion structure…”
Section: Continuum Segregation Equation For Bidisperse Mixturesmentioning
confidence: 99%
“…Bridgwater, Foo & Stephens 1985;Savage & Lun 1988;Bridgwater 1994;Dolgunin & Ukolov 1995;Gray & Thornton 2005;Gray & Chugunov 2006;Thornton et al 2006;May, Shearer & Daniels 2010) all share a similar advection-diffusion structure…”
Section: Continuum Segregation Equation For Bidisperse Mixturesmentioning
confidence: 99%
“…13,28,29 In the papers cited the segregation rate is assumed to be proportional to the local shear rate and the experimentally determined velocity profiles are used to solve the continuum model. In these experiments it was not possible to monitor the local volume fraction of the small particles directly, and it had to be inferred via the measured expansion and compaction of the sample.…”
Section: Previous Comparison To the Theorymentioning
confidence: 99%
“…Golick and Daniels [72] and May et al [104] performed ring shear segregation experiments which showed that under a confining pressure both the velocity profile, u = u(z), and the segregation rate, q = q(z), could have a strong height dependence and exact solutions for this case have been constructed [104,105]. Another interesting feature of these experiments is that they measured the degree of segregation based on the rise and fall of the top plate, which was caused by the grains packing denser in a mixed state than in a pure phase.…”
Section: Segregation In Bidisperse Mixturesmentioning
confidence: 99%